Gender and STEM background as predictors of college students' competencies in forming research questions and designing experiments in inquiry activities. Issue 17 (22nd November 2021) - Cheng, Li-Ting; Smith, Thomas J.; Hong, Zuway-R.; Lin, Huann-shyang
ABSTRACT: This study examined the roles of gender and STEM major status as predictors of performance in formulating a research question and designing experiment among 70 undergraduate Taiwanese college students participating in inquiry-based learning (IBL). Student participants in this study were involved in discrepant demonstrations of scientific events and hands-on activities to introduce conceptual knowledge with the goal of motivating their learning interest in explaining phenomena scientifically. In addition, historical cases of scientific inquiry were utilised to scaffold and support inquiry procedures. At three time points during the semester, learning sheets were used to assess student performance in scientific inquiry practices (generating research questions and designing experiment). Results revealed that female students showed greater ability to form a research question than males. Additionally, while female science majors showed greater ability to generate a research design than female non-science majors, the opposite was true for males. Finally, the challenges and difficulties encountered by students in formulating research question and designing experiments are addressed. The findings of students' significant and positive progress on formulating research question in the three consecutive assessments reveal the potential benefits of pedagogical approaches used in this study. On the other hand, the variety of students' learning outcomes provide insight into potential ways that specific student subgroups may respond to pedagogies within an inquiry-based context. The initial findings also provide a starting point for instructors to begin debating the most productive ways of planning and delivering scientific inquiry instruction.